UAV Based Agricultural Planning and Landslide Monitoring - Yaprak, Servet; Yildirim, Ömer; Susam, Tekin (TeMA - Journal of Land Use, Mobility and Environment, 2017)
The use of Unmanned Aerial Vehicle (UAV) tools has become widespread in map production, land surveying, landslide, erosion monitoring, monitoring of agricultural activities, aerial crop surveying, forest fire detection and monitoring operations. In this study, GEO 2 UAV manufactured by TEKNOMER equipped with SONY A6000 camera has been used. The flight plan have been performed with 100 m altitude, with 80% longitudinal and 60% side overlapping. Ground Control Points (GCPs) have been observed with Topcon and Trimble GNSS geodetic receivers. Recorded GNSS signals have been processed with LGO V.8.4 software to get sensitive location information. 985 photos have been taken for the 344 hectares the agricultural area. 291 photos have been taken for 50 hectares the landslide area. All photos were processed by PIX4D software. For the agricultural area, 25 GCPs and for the landslide area, 8 GCPs have been included in the evaluation. 3D images were produced with pixel matching algorithms. As a result, the RMS evaluation was obtained as ±0.054 m for the agricultural area and as ±0.018 m for the landslide area. UAV images have indisputable contributions to the management of catastrophes such as landslides and earthquakes, and it is impossible to make terrestrial measurements in areas where disaster impact continues.